Finance and Development, June 2013. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper highlights that one of the most dramatic developments in the 20th century was the entry of women into economic and political spheres previously occupied almost exclusively by men. Although women are making progress in eliminating gender disparities, they still lag men in the workplace and in the halls of government. These gaps are found throughout the world, but are particularly pronounced in developing economies. So far, the greatest success has been in reducing education and health disparities and the least in increasing women's economic and political influence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet